Geotechnologies Applied to the Management and Preservation of Cultural and Natural Heritage: A Case Study of Morro do Rangel, Rio de Janeiro/RJ - Coelho, Renato Ferraz de Mendonça; Carriello, Felix (Latin American Journal of the Built Environment & Sustainability, 2025)
Objective - This study analyzed the land use and land cover of Morro do Rangel, a listed natural and cultural heritage site in Rio de Janeiro, with the goal of assessing its preservation over time and proposing management strategies based on geotechnologies.Methodologies - Historical shapefiles, high-resolution satellite imagery, and geoprocessing applications (QGIS and ArcGIS) were used, applying a theoretical approach that integrates geoconservation, remote sensing, and territorial analysis of listed properties.Originality/Relevance - The study fills gaps in the monitoring of these heritage sites, offering a replicable and academically relevant methodology at the intersection of cultural preservation and spatial technologies.Results - The results indicated relative stability of the listed territory, increased tree and shrub cover, specific expansion of irregular urban settlements, and identification of areas vulnerable to real estate speculation, highlighting opportunities for reforestation and heritage education.Theoretical/Methodological Contributions - The research demonstrates the effectiveness of geoprocessing and remote sensing as tools for spatial analysis, monitoring, and intervention planning.Social and Environmental Contributions - These contributions are also important for the development of public policies, environmental education, and heritage conservation, promoting a balance between urban growth and environmental preservation.
Keywords: heritage; Geoprocessing; Remote sensing